Occupational differences in SARS-CoV-2 infection: the Japan COVID-19 and Society Internet Survey (JACSIS) study in 2022 - Ayane Sato; Hirokazu Tanaka; Takahiro Tabuchi; Kota Katanoda (BMC, 2024)
Abstract Background During the coronavirus disease (COVID-19) pandemic, essential workers (e.g. medical workers) may be at a high prevalence of contracting COVID-19; however, the trend remains unclear in Japan. This study aimed to investigate occupational differences in the prevalence of COVID-19. Methods Data were retrieved from the 2022 Japan COVID-19 and Society Internet Survey. We analyzed the self-reported SARS-CoV-2 infection as of October 2022. We included 21,875 participants aged 20-64 years. Participants were classified into five occupation groups ("medical workers," "off-site medical workers," "care workers," "other essential workers", and "non-essential workers"), as well as those unemployed. The prevalence ratio of COVID-19 was computed using Poisson regression. We included sex, age, SARS-CoV-2 vaccination history, number of households, education level, and residential area as covariates. Additionally, we performed similar analyses for three time periods: (1) August-September 2022, (2) October 2021 to July 2022, and (3) before September 2021. Results The overall cumulative prevalence of COVID-19, as of October 2022, was 16.5%. Regarding occupation, medical workers had a higher prevalence than non-essential workers (23.5% vs 16.2% (difference: 7.2% point [95% confidence interval (CI): 4.2-10.2])). Similar results were observed among care workers compared with non-essential workers (22.1% vs 16.2% (difference: 5.9% point [95% CI: 2.5%-9.3%])). Other essential workers had a similar prevalence to non-essential workers (17.6% vs 16.2% (difference: 1.4% point [95% CI: -0.1%-2.8%]). In relative terms, medical workers and care workers were associated with an increased prevalence of COVID-19 (prevalence ratio: 1.44 [95% CI: 1.20-1.73] and 1.36 [95% CI: 1.11-1.66], respectively). In addition, we found that younger age, living in endemic region (e.g., Tokyo and Osaka), and living with more than four people contributed to the higher prevalence. According to the time period, the prevalence was significantly higher in medical and care workers than in non-essential workers only during August-September 2022, which corresponded to the severest outbreak period in Japan. Conclusions In Japan, medical and care workers had a higher prevalence of contracting COVID-19 compared to non-essential workers. However, this trend emerged during the peak of the COVID-19 spreading in the summer of 2022.